1980
DOI: 10.1021/bi00542a023
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric evolutionary homology revealed by the study of protocatechuate 3,4-dioxygenase from Azotobacter vinelandii

Abstract: Protocatechuate 3,4-dioxygenase (EC 1.13.1.3) was purified to homogeneity from extracts of Azotobacter vinelandii. The molecular weight of the oligomeric protein was estimated to be 510 000 by gel filtration and 480 000 by ultracentrifugation. The oligomer appears to be formed by association of equal amounts of nonidentical subunits which were estimated by sodium dodecyl sulfate gel electrophoresis to have respective molecular weights of 23 300 and 25 250. Ten gram-atoms of iron was associated with each mol of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 33 publications
1
44
0
1
Order By: Relevance
“…Pseudomonas aeruginosa resembles P. putida in many respects and elaborates closely homologous structural genes (Pate1 & ) that appear to be organized and transcribed in a roughly similar fashion (Kemp & Hegeman, 1968). Azotobacter species possess pca structural genes that are homologous to their P. putida counterparts, and P-ketoadipate elicits a similar inducible response in these two biological groups (Durham & Ornston, 1980). Therefore it will be of interest to determine if homologues of pcaR govern gene expression in Azotobacter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa resembles P. putida in many respects and elaborates closely homologous structural genes (Pate1 & ) that appear to be organized and transcribed in a roughly similar fashion (Kemp & Hegeman, 1968). Azotobacter species possess pca structural genes that are homologous to their P. putida counterparts, and P-ketoadipate elicits a similar inducible response in these two biological groups (Durham & Ornston, 1980). Therefore it will be of interest to determine if homologues of pcaR govern gene expression in Azotobacter.…”
Section: Discussionmentioning
confidence: 99%
“…1). The pathway is distributed widely among bacteria, and comparative studies indicate that structural genes for the pathway in biologically distant prokaryotic groups have evolved from a single ancestral set (Durham & Ornston, 1980;Durham et al, 1980;Yeh etal., 1980a, b;Yeh &Omston, 1981). The divergent genes have fallen under different forms of transcriptional control Stanier & Ornston, 1973;Ornston & Parke, 1977;Cain, 1980;Parke & Ornston, 1986) and thus gene rearrangement appears to have played a significant role in the evolution of the pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Both these enzymes are well characterized and found to be heterodimers with α and β subunits and requires Fe +2 for their activity [32,64,67,76,104,109,111,112]. Some of them are reported to be octamers or decamers [5,25,105,108]. In Pseudomonas aeruginosa, protocatechuate 3,4-dioxygenase is a octamer, each subunit of octamer has two α and two β subunits with molecular weight of 22.5 and 25 kD, respectively.…”
Section: Protocatechaute Dioxygenasementioning
confidence: 99%
“…Both intradiol and extradiol ring cleavage dioxygenases operate in degradation pathways that convert aromatic compounds such as tyrosine and 4-hydroxyphenylacetate to tricarboxcylic acid cycle intermediates (3,7,43,44). DNA and amino acid sequence analyses have shown that the intradiol and extradiol dioxygenases are evolutionarily distinct (15,20,23). There now appear to be at least three phylogenetically distinct families of extradiol dioxygenases (2).…”
mentioning
confidence: 99%